2010
DOI: 10.1111/j.1439-0523.2010.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of resistance in bread wheat to Russian wheat aphid (Diuraphis noxia) in Syria identified using the Focused Identification of Germplasm Strategy (FIGS)

Abstract: Russian wheat aphid, Diuraphis noxia (Kurdjumov), is an important pest of wheat and barley in North America, Africa and the Middle East. Host plant resistance is the most economical and practical means of controlling this insect. Field and greenhouse screening in Syria of bread wheat lines from the International Center for Agricultural Research in the Dry AreasÕ (ICARDA) gene bank, using the Focused Identification of Germplasm Strategy (FIGS), identified 12 lines resistant to D. noxia. These sources of resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 9 publications
3
40
0
Order By: Relevance
“…Wheat germplasm collected from regions where RWA is endemic provides fundamental materials for genetic improvement of RWA resistance to help ensure food security for the world's rapidly growing population (El Bouhssini et al, 2011). Advances in translational genomics have highlighted the need of homogeneous resistance sources for gene mapping, gene cloning, and molecular breeding.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat germplasm collected from regions where RWA is endemic provides fundamental materials for genetic improvement of RWA resistance to help ensure food security for the world's rapidly growing population (El Bouhssini et al, 2011). Advances in translational genomics have highlighted the need of homogeneous resistance sources for gene mapping, gene cloning, and molecular breeding.…”
Section: Resultsmentioning
confidence: 99%
“…[38], Russian wheat aphid ( Diuraphis noxia Kurdj.) [39] and stem rust ( Puccinia graminis Pers.) [34], [35] as well as net blotch ( Pyrenophora teres Drechs.)…”
Section: Introductionmentioning
confidence: 99%
“…The FIGS approach assumes a predictive link between some eco‐geographic parameters of the original collecting site of germplasm (with focus on landraces and crop wild relatives) and a target adaptive trait, such as disease resistance. Recent studies have proposed the algorithms and methods for implementation of trait mining using FIGS (El Bouhssini et al, 2009, 2011; Endresen, 2010; Endresen et al, 2011; Bari et al, 2011). Zeven (1998) presented a review of definitions and classifications for landraces and suggested the definition provided by Mansholt (1909), which reads, “an autochthonous landrace is a variety with a high capacity to tolerate biotic and abiotic stress, resulting in a high yield stability and an intermediate yield level under a low input agricultural system” (Zeven 1998, 137).…”
mentioning
confidence: 99%
“…The rationale or fundamental theory for trait mining using FIGS is that crop traits are linked to the eco‐climatic environment associated with the collecting site of accessions and that this link can be exploited to build predictive models to identify a subset of accessions with a higher likelihood of holding a target trait property (Mackay and Street, 2004). The first studies to validate the FIGS approach were conducted using a heuristic approach in which expert knowledge from the scientific literature was used to identify the boundaries for each of the eco‐climatic variables (Street et al, 2008; Bhullar et al, 2009; El Bouhssini et al, 2009, 2011). Other studies were designed to calibrate a predictive computer model to validate the FIGS approach (Endresen, 2010; Endresen et al, 2011).…”
mentioning
confidence: 99%